Metabolic Syndrome in Preeclampsia Women in Gorgan - Rafeeinia, Arash (Open Biochem J, 2014)
The aim of study was to assess the metabolic syndrome in preeclampsia women. The study was performed on 50 women. The metabolic syndrome prevalence was 66%. Serum glucose, triglyceride and LDL-cholesterol levels significantly were increased and HDL- cholesterol level significantly was decreased in metabolic syndrome patients. These patients showed high prevalence of components of the syndrome. Our results show the importance of dyslipidemia in preeclampsia in overweight and obese women. Preeclampsia and cardiovascular disease are important problems for the health of women. It may be useful to give a treat to people with a high-normal blood pressure in early pregnancy.